A Cost-Oriented Scheme for Reconstruction and Efficient Insulation of Medium- and High-Voltage Stator Coils - Mohammad Ali Taheripour; Ahmad Darabi; Mojtaba Shivaie (AUT Journal of Electrical Engineering, 2025)
In today’s industrial world, it is indispensable to offer a correlated equilibrium between the reconstruction costs of damaged electric motors and desirable of performance characteristics so as to exploit available primary materials. This paper presents a cost-oriented scheme to choose an effective insulation method in reconstructing the medium- and high-voltage stator coils in both vacuum pressure impregnation and resin-rich methods. The insulations required in coil reconstruction include three sections: strand, group, and main body insulation. These insulations have specific electrical characteristics and dimensions that limit their use in a specific part of the coil. On the other hand, sometimes these insulations are not available or it is difficult to get them. Because of this, their prices are constantly changing, and it is very difficult to estimate the cost of materials relatively accurately. In this paper, various designs are produced by combining available insulation from each section. Then, mathematical models will be extracted to check the functional characteristics and costs of renovation materials in the plans. Ultimately, the best reconstruction design, changes in performance characteristics compared to insulations with different specifications is selected and the sensitivity of the cost of the designs to the cost of insulation materials and the effects caused by Remove group insulation is checked. For validation, the results associated with the reconstruction calculations of a damaged realistic 6-kV 535-kW electric motor are presented.